2015
DOI: 10.1249/mss.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Benign Prostatic Hyperplasia-Related Outcomes and Nocturia

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
1
27
0
5
Order By: Relevance
“…[3,12,15,33] Men who are physically active are at lower risk of nocturia, the most common and bothersome of LUTS. [34] Indeed, a meta-analysis of 11 published studies with over 43,000 men found that moderate to vigorous physical activity reduced the risk of LUTS by as much as 25% compared to a sedentary lifestyle, with stronger effects seen with higher levels of activity. [35] In addition, a greater physical activity at baseline predicted improvement in LUTS symptoms in a 5 year prospective study of 780 men, aged 35 to 80 at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…[3,12,15,33] Men who are physically active are at lower risk of nocturia, the most common and bothersome of LUTS. [34] Indeed, a meta-analysis of 11 published studies with over 43,000 men found that moderate to vigorous physical activity reduced the risk of LUTS by as much as 25% compared to a sedentary lifestyle, with stronger effects seen with higher levels of activity. [35] In addition, a greater physical activity at baseline predicted improvement in LUTS symptoms in a 5 year prospective study of 780 men, aged 35 to 80 at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) is the most common pathologic and clinical abnormality associated with the prostate. It is estimated that histologic BPH lesions are encountered in men as young as in their 20s and 30s and the disease continues to rise as they age [Wolin et al, ]. Epidemiological data indicate that asymptomatic BPH affects 50% of all men by the time they turn 50 and escalates to >90% in men 85 years or older [Oesterling, ].…”
Section: The Integrated Modelmentioning
confidence: 99%
“…BPH is the most common pathologic and clinical abnormality associated with the prostate gland. Indeed, histologic BPH lesions are encountered in men as young as in their 20s and 30s and the prevalence of the disease continues to rise as they age [ 26 ]. Although accurate estimates like those available for PCa are not available for BPH, epidemiological data indicate that asymptomatic BPH affects 50% of all men by the time they turn 50, and escalates to >90% in men 85 years or older [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%